INTERNET OF THINGS (IoT) BASED REMOTE SURVEILLANCE CAMERA FOR SUPERVISION OF EXAMINATIONS - ODEYEMI, CHARITY segun; OMODUNBI, Bolaji Abigail; OLANIYAN, Olatayo Moses; SOLADOYE, Afeez A. (LAUTECH Journal of Engineering and Technology, 2024)
Remote surveillance camera is used for detecting and averting illegal or suspicious activities in cities, campuses, businesses places, large gathering and many other places. University examinations are faced with challenges of malpractices due to stress and inadequate number of human invigilators. The Internet of Things (IoT) based remote surveillance camera system was developed to monitor students’ conduct in examination hall using ESP32 CAM project development board with an on-board camera for video capturing. It was programed with the Future Technology Device International (FTDI), powered with 5v dc and the Ngrok application was developed and used to access the system output remotely on internet. The system was tested for surveillance from a remote distance over a local area network (LAN) and over the internet which yielded satisfactory results. Also when the captured image was fed into a trained face recognition model, the candidate was recognized by name and matriculation number. The conduct of examination can be effectively monitored in a wireless network over the local area network (LAN) and the wide area network (WAN) using the developed IoT based remote surveillance camera system for a closed supervision. This will help to detect and reduce all forms of malpractices in examination hall.